How Health Anxiety is Associated with Perceived Risk of Reinfection Among COVID-19 Infected People After the Epidemic Control Measures Lifted in China: A Multiple Mediating and Multi-Group Analysis - Zhao W; Ding N; Hu H; Tian W; He J; Du M; Zhao C; Zhang G (Psychology Research and Behavior Management)
Wenqian Zhao,1,2,* Ningning Ding,2,* Haiyan Hu,2 Wenwen Tian,2 Jiankang He,2 Mingxuan Du,2 Chengjia Zhao,3 Guohua Zhang2,4,5 1Cixi Biomedical Research Institute, Wenzhou Medical University, Ningbo, 315302, People’s Republic of China; 2Department of Psychology, School of Mental Health, Wenzhou Medical University, Wenzhou, 325035, People’s Republic of China; 3School of Education, Renmin University of China, Beijing, 100872, People’s Republic of China; 4Zhejiang Provincial Clinical Research Center for Mental Health, The Affiliated Kangning Hospital of Wenzhou Medical University, Wenzhou, 325007, People’s Republic of China; 5Wenzhou Key Laboratory of Basic and Translational Research for Mental Disorders, Wenzhou, Zhejiang, 325035, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guohua Zhang, Email zghcnu@wmu.edu.cnBackground: After the lifting of epidemic control measures in China at the end of 2022, the number of COVID-19 infections has increased dramatically. Such an upsurge may intensify people’s health anxiety and raise concerns about the risk of reinfection. While numerous studies have shown the correlation between them during the COVID-19, research on their underlying mechanism remains limited.Purpose: This study aims to test the relationship and mechanism between health anxiety and perceived risk of reinfection among COVID-19 infected people from different occupational backgrounds.Methods: A cross-sectional study was conducted from December 24th to 28th, 2022, after the epidemic control measures were lifted. A total of 1122 Chinese individuals were infected with COVID-19 (67.91% females, Mage = 28.13) completed measures of health anxiety, perceived risk of reinfection, fear of COVID-19, online health information seeking (OHIS), and COVID-19 information fear of missing out (FOMO). Data were analyzed using multiple-mediation model and multi-group analysis.Results: Health anxiety, perceived risk of reinfection, fear of COVID-19, OHIS and COVID-19 information FOMO were positively and significantly related to each other (r ranged from 0.25 to 0.77, all p < 0.001). Fear of COVID-19 (β = 0.27, p < 0.01), OHIS (β = 0.10, p < 0.001), and COVID-19 information FOMO (β = − 0.05, p < 0.01) fully mediated the relationship between health anxiety and perceived risk of reinfection, the path of chaining mediation is also significant. Discrepancies in mediation models surfaced across the three types of work groups.Conclusion: Findings suggest fear of COVID-19, OHIS and COVID-19 information FOMO may play significant mediating roles in explaining the relationship between health anxiety and perceived risk of reinfection. Interventions to reduce the perceived risk of reinfection should aim to improve the quality of online health information and individuals’ online health literacy and reduce fear of COVID-19 during and after the pandemic.Keywords: health anxiety, perceived risk of reinfection, fear of COVID-19, COVID-19 information FOMO, online health information seeking, people infected with COVID-19